La diffusione dei culti ungheresi tra i domenicani di Dubrovnik (Ragusa) nel tempo di Mattia Corvino - Marinković, Ana (Array, 2008)
Although Ragusan Republic recognised the sovereignity of Hungarian Kings from 1358 to 1527, the curious concentration of artefacts and documents witnessing veneration of Hungarian saints of the royal lineage in the Dominican monastery in Dubrovnik dates from the late period of Matthias' reign. The cult of St. Margaret of Hungary can be related to the two most influential Ragusan Dominicans of the period, Seraphinus de Bona and Thomas de Basilio, who were invited by King Matthias to help the foundation of Dominican studium generale in Buda, and introduced veneration of the Hungarian Dominican cult upon their return to Dubrovnik. The altar dedicated to Sts. Stephen, Ladislas and Emeric was erected in the monastic chapterhouse by a branch of patrician family de Goze whose members had close ties with Hungarian court, as attested in contemporary records. The seemingly abrupt appearance of Hungarian cults is not at all surprising considering Matthias' help with lasting Ragusan Dominicans' efforts for seceding from Dalmatian (Venetian) Province, which plausibly opened a path to veneration of Hungarian saints, provoking, in addition, Ragusan diplomats to express their bonds with the Hungarian royal court in a new way. Thus, the veneration of Hungarian saints reflects the range of connections between the Kingdom and the Republic: the diplomats were prone to choose the cults of Hungarian kings, whereas Dominican monks opted for the ever growing cult of the Dominican nun.